GIGAPIXEL PHOTOGRAPHY FOR HIGH-ACCURACY FACADE DOCUMENTATION: MAPPING THE ORIGINAL LOCATION OF THE FORMA URBIS ROMAE - Jones, K.; Bevan, G.; Talbert, R.; Wolfram Thill, E.; Lehoux, D. (International archives of the photogrammetry, remote sensing and spatial information sciences., 2023)
The Forma Urbis Romae was a monumental marble map of ancient Rome from the Severan Dynasty. It was originally attached to the interior wall of the Temple of Peace, but through the course of the Middle Ages the marble panels of the map fell off or were deliberately removed. They have been found mainly in the vicinity of the Forum, but only about 10% of the original surface have been discovered. The wall on which the map was mounted is currently an exterior wall of the Church of SS. Cosma e Damiano, and the original holes from the iron nails used to attach the marble panels of the map are still visible on unrestored areas. In order to attempt a full reconstruction of the map from the fragments, detailed measurements of the positions of the mounting holes are required. Access to the wall itself is difficult because of its height, and surrounding construction and excavation. A method was needed to map the surface of the wall without the expense and complication of erecting scaffolding for direct hand-measurement. To this end, digital photogrammetry and gigapixel photography with a telephoto lens were combined to produce stereo-models from the street level 50 m away. From these stereo-models of merged panoramic images in excess of 200 megapixels and a Ground Sample Distance of 1 mm it was possible to use stereo-plotting to create a map of archaeologically relevant features that will serve as the foundation for determining the positions of the surviving marble pieces.